2018
DOI: 10.1080/14767058.2018.1439009
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of changes in biochemical composition of fetal brain between 18th and 40th gestational week in proton magnetic resonance spectroscopy

Abstract: Changes in the H MRS spectrum are visible with increasing age of the fetus. All studied substances in fetal brain change their concentrations during pregnancy, which may be associated with the synaptic and dendritic development as well as myelination. Knowledge about the chemical changes in the fetal brain can provide valuable information in studies of the mechanisms of pregnancy and fetal development, define steps of brain metabolic development and explain reasons of pathologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The physiological and gestational age-related variability of metabolite levels in healthy fetuses has been previously described in detail. According to Urbanik et al, a significant rise can be detected in NAA, Cr, Cho, and mI absolute concentrations throughout gestation (weeks 18–40) 7 . This observation is partly confirmed by Kok et al, also describing increasing NAA absolute levels between gestational weeks 30–41, further adding that, while NAA/Cr and NAA/Cho ratios also rise in the examined gestational period, Cho/Cr ratio decreases, suggesting that absolute metabolite levels do not elevate uniformly and with the same velocity throughout physiological neuronal maturation 13 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The physiological and gestational age-related variability of metabolite levels in healthy fetuses has been previously described in detail. According to Urbanik et al, a significant rise can be detected in NAA, Cr, Cho, and mI absolute concentrations throughout gestation (weeks 18–40) 7 . This observation is partly confirmed by Kok et al, also describing increasing NAA absolute levels between gestational weeks 30–41, further adding that, while NAA/Cr and NAA/Cho ratios also rise in the examined gestational period, Cho/Cr ratio decreases, suggesting that absolute metabolite levels do not elevate uniformly and with the same velocity throughout physiological neuronal maturation 13 .…”
Section: Discussionmentioning
confidence: 98%
“…However, the effect of the newborns’ postnatal age on the predictive value of H-MRS throughout the first weeks of life has not been studied in detail, albeit examination of all newborns with HIE in a uniform postnatal narrow age window is not plausible, due to variable clinical stability and available resources. Moreover, existing evidence proposes that metabolite ratios may also be affected by gestational age 7 . The influence of neither of these factors has been studied so far on the predictive value of H-MRS, even though accurate description of metabolite dynamics would be essential, especially by investigating metabolite ratios registered conventionally, to ensure generalizability.…”
Section: Introductionmentioning
confidence: 99%
“…Multiparametric approaches have potential value for quantitative evaluation fetal brain development. In proton magnetic resonance spectroscopy (H‐MRS), altered metabolite concentrations in the fetal brain may be associated with myelin formation 34 . The multiple parameters of diffusion were used to quantify microstructural changes in white matter and have been applied to fetal white matter development studies 35 .…”
Section: Discussionmentioning
confidence: 99%
“…In proton magnetic resonance spectroscopy (H-MRS), altered metabolite concentrations in the fetal brain may be associated with myelin formation. 34 The multiple parameters of diffusion were used to quantify microstructural changes in white matter and have been applied to fetal white matter development studies. 35 Yarnykh et al 36 used macromolecular proton fraction (MPF) mapping to quantitatively assess fetal brain myelination and concluded that myelin was the main determinant of MPF in brain tissue, and MPF mapping is sensitive to the early stages of fetal brain myelin formation and can be clinically applied.…”
Section: Measured the Apparentmentioning
confidence: 99%
“…A recent cross-sectional study aimed to characterize the development of metabolite spectra during gestation and observed choline and myo-inositol peaks emerging first at 18 weeks gestation, followed by N-acetylaspartate and creatine peaks at 23 weeks; adjacent to the N-acetylaspartate, a glutamate signal was detected at GA 29. All metabolites increase in concentration with gestation (Urbanik, Cichocka, Kozub, Karcz, & Herman-Sucharska, 2019).…”
Section: Neuroimaging Targets For Biomarkers Of Neuropsychiatric Diseasementioning
confidence: 99%